2014
DOI: 10.1371/journal.pntd.0003334
|View full text |Cite|
|
Sign up to set email alerts
|

Standardizing Visual Control Devices for Tsetse Flies: East African Species Glossina fuscipes fuscipes and Glossina tachinoides

Abstract: BackgroundRiverine species of tsetse are responsible for most human African trypanosomiasis (HAT) transmission and are also important vectors of animal trypanosomiasis. This study concerns the development of visual control devices for two such species, Glossina fuscipes fuscipes and Glossina tachinoides, at the eastern limits of their continental range. The goal was to determine the most long-lasting, practical and cost-effective visually attractive device that induces the strongest landing responses in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Further, tiny targets when mounted on pirogues moving along a river have proved to be effective in reducing tsetse density [ 73 ]. The development of such novel control tools, as well as standardization of existing models, will lead to identification of cost-effective devices for tsetse management [ 70 , 74 , 75 ].…”
Section: Emerging Options In Disease and Vector Controlmentioning
confidence: 99%
“…Further, tiny targets when mounted on pirogues moving along a river have proved to be effective in reducing tsetse density [ 73 ]. The development of such novel control tools, as well as standardization of existing models, will lead to identification of cost-effective devices for tsetse management [ 70 , 74 , 75 ].…”
Section: Emerging Options In Disease and Vector Controlmentioning
confidence: 99%
“…However, other explanations must not be ruled out, such as a separate role for low luminance in attraction, or the involvement of polarotaxis for which dark surfaces are particularly effective in providing polarised light cues [ 20 , 46 ]. Studies of a range of Glossina species have reported decreased catches using blue/black combination e-cloths, when the cloth panels inside the electrocuting grids were covered by an adhesive sheet that absorbed UV wavelengths [ 47 , 48 , 49 ]. This resulted from decreased tsetse catch over the black portion of the cloth panel only.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies the UV reflectance of the black cloth was low, meaning that this result is unlikely to be explained by an effect of the UV manipulation on the R7p mechanism described in the current analysis. Since the adhesive film absorbed wavelengths below 400 nm [ 49 ], it would have affected not only the repellent R7p response (shorter wavelength UV), but also the attractive R7y response (UV-blue), and may thus have had complex effects on the mechanism of attraction. It is also possible that the adhesive sheet affected other visual cues, such as the polarisation of reflected light [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the addition of a UV absorber in the glue. In addition, spectrophotometric measurements of light reflected from adhesive film applied onto the same fabrics used in this study indicate that all wavelengths in the UV range were mostly absorbed by the fabrics [ 43 ]. In the 2010 Angolan trial, a 1 x 1 m square of adhesive film alone (without any cloth backing) was compared to cloth targets with adhesive film attached to both sides to ascertain whether adhesive film in itself attracts flies.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research on riverine or Palpalis group tsetse has shown that much smaller targets (0.25–0.5 m 2 ) can capture more flies per m 2 than larger targets and would be more cost-effective in programmes targeting species such as Glossina fuscipes fuscipes and G . palpalis palp alis [ 40 43 ]. In contrast, for savannah species such as G .…”
Section: Introductionmentioning
confidence: 99%